Ifosfamide toxicity to the retina and the possible roles of lecithin and quercetin in albino rats - Ahmed, Rehab; Aly, Eman; Mahmoud, Sherif; Awad, Sahar; Kamal, Gehan (International Journal of Engineering and Technology, 2018)
Background: During cancer chemotherapy, drug-induced oxidative stress can limit therapeutic efficiency and cause a number of side effects. Objectives: Our study aimed to characterize the side effects of an alkylating agent chemotherapy ifosfamide to the retina and if the supplementation of lecithin and or quercetin can diminish its oxidative stress by means of comet assay and FTIR.Methods: Seventy female albino rats divided as control, rats given orally quercetin or lecithin, rats injected with ifosfamide, rats given quercetin or lecithin and in combination of them with ifosfamide injection.Results: Lecithin and quercetin groups indicate a normal comet parameters and distribution of protein secondary structure components content of Î²-turn, Î±-helix and Î²-sheet. After Ifosfamide injection, all comet parameters and Î²-Turns content were significant increase (pË‚0.05) with the same context significant decrease (pË‚0.05) of Î±-helix was observed. Lecithin or quercetin reduces the effect of ifosfamide injection in tail length and percentage tailed DNA. Combined treatment gives more protection against DNA damage. Lecithin role is cleared in returning the normal distribution of Î²-turn, Î±-helix, Î²-sheet and lack of protective effect of quercetin regarding the protein secondary structure of retina was observed.Conclusion: We suggest using lecithin and quercetin in combined treatment to reduce the oxidative stress due to ifosfamide.